Cardiac contractility modulation improves long-term survival and hospitalizations in heart failure with reduced ejection fraction - Anker, Stefan; Borggrefe, Martin; Neuser, Hans; Ohlow, Marc-Alexander; Röger, Susanne; Goette, Andreas; Remppis, Bjoern-Andrew; Kuck, Karl-Heinz; Najarian, Kevin B.; Guttermann, David D.; Rousso, Benny; Burkhoff, Daniel; et al. (European journal of heart failure, 2019)
AIMS: Cardiac contractility modulation (CCM) improves symptoms and exercise tolerance and reduces heart failure (HF) hospitalizations over 6-month follow-up in patients with New York Heart Association (NYHA) class III or IV symptoms, QRS < 130 ms and 25% ≤ left ventricular ejection fraction (LVEF) ≤ 45% (FIX-HF-5C study). The current prospective registry study (CCM-REG) aimed to assess the longer-term impact of CCM on hospitalizations and mortality in real-world experience in this same population. - METHODS AND RESULTS: A total of 140 patients with 25% ≤ LVEF ≤ 45% receiving CCM therapy (CCM-REG25-45 ) for clinical indications were included. Cardiovascular and HF hospitalizations, Minnesota Living with Heart Failure Questionnaire (MLHFQ) and NYHA class were assessed over 2 years. Mortality was tracked through 3 years and compared with predictions by the Seattle Heart Failure Model (SHFM). A separate analysis was performed on patients with 35% ≤ LVEF ≤ 45% (CCM-REG35-45 ) and 25% ≤ LVEF < 35% (CCM-REG25-34 ). Hospitalizations decreased by 75% (from 1.2/patient-year the year before, to 0.35/patient-year during the 2 years following CCM, P < 0.0001) in CCM-REG25-45 and by a similar amount in CCM-REG35-45 (P < 0.0001) and CCM-REG25-34 . MLHFQ and NYHA class improved in all three cohorts, with progressive improvements over time (P < 0.002). Three-year survival in CCM-REG25-45 (82.8%) and CCM-REG24-34 (79.4%) were similar to those predicted by SHFM (76.7%, P = 0.16; 78.0%, P = 0.81, respectively) and was better than predicted in CCM-REG35-45 (88.0% vs. 74.7%, P = 0.046). - CONCLUSION: In real-world experience, CCM produces results similar to those of previous studies in subjects with 25% ≤ LVEF ≤ 45% and QRS < 130 ms; cardiovascular and HF hospitalizations are reduced and MLHFQ and NYHA class are improved. Overall mortality was comparable to that predicted by the SHFM but was lower than predicted in patients with 35% ≤ LVEF ≤ 45%.